2009
DOI: 10.1161/circinterventions.108.819722
|View full text |Cite
|
Sign up to set email alerts
|

Factors Portending Endoleak Formation After Thoracic Aortic Stent-Graft Repair of Complicated Aortic Dissection

Abstract: Background-Endoleaks after stent-graft repair of aortic dissections are poorly understood but seem substantially different from those seen after aneurysm repair. We studied anatomic and clinical factors associated with endoleaks in patients who underwent stent-graft repair of complicated type B aortic dissections. Methods and Results-From 2000 to 2007, 37 patients underwent stent-graft repair of acute (Յ14 days; nϭ23), subacute (15 to 90 days; nϭ10) or chronic (Ͼ90 days; nϭ4) complicated type B aortic dissecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 37 publications
4
47
0
1
Order By: Relevance
“…Different predictors of endoleak have been analyzed in the literature, 5,6,8,9,[20][21][22] including male gender, larger aneurysm size, length of aorta covered by the stent graft, number of stents used, proximal landing zone, and aortic arch morphology. The predictive value of a number of these factors is still controversial, notably aorta length covered by stent graft, considered protective of proximal endoleak by Verhoye et al 9 and, on the contrary, predictive of endoleak by Parmer et al and Morales et al 21,22 In all these studies, results were based only on univariable analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different predictors of endoleak have been analyzed in the literature, 5,6,8,9,[20][21][22] including male gender, larger aneurysm size, length of aorta covered by the stent graft, number of stents used, proximal landing zone, and aortic arch morphology. The predictive value of a number of these factors is still controversial, notably aorta length covered by stent graft, considered protective of proximal endoleak by Verhoye et al 9 and, on the contrary, predictive of endoleak by Parmer et al and Morales et al 21,22 In all these studies, results were based only on univariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have led some authors to modify their criteria of proximal aortic neck length in case of zone 1 endografting to 30 mm or more. 24,25 Furthermore, numerous studies 5,6,8,21 report landing zone 2 as anatomically unsuitable for stent graft implantation because it can favor endoleak. These authors argue, first, that LSA overstenting exposes the stent graft to abrupt angulation with, in consequence, excessive mechanical stress acting on the stent and incomplete apposition of the devices, thus incurring a risk of type I endoleak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the therapeutic goal for patients with complicated type B dissections is not so much to eliminate all blood flow in the false lumen as to reperfuse the lower body and prevent thoracic aortic rupture. 5,6 The remaining pressurized false lumen has been a critical problem in chronic phase type B dissection, and several investigators have suggested that the single most significant cause of death related to aortic dissection is expansion of the false lumen leading to aneurysm and rupture. 4,7 Akutsu et al 4 reported that in the chronic period patients with a thrombosed false lumen had a significantly better outcome in terms of dissection-related death and dissection-related events.…”
Section: Discussionmentioning
confidence: 99%
“…1 Experimental and clinical data have shown that poor endograft apposition within the aortic arch increases the risk of technical failure after TEVAR. 2 Endoanchors represent a feasible option to enhance proximal and/or distal endograft alignment. Although the risk of embolic debris caused by endoanchor placement has been emphasized, endoanchor dislocation from the endograft after TEVAR has not yet been described.…”
mentioning
confidence: 99%